2017
DOI: 10.1007/s10120-017-0776-8
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the celiac branch of the vagal nerve for pylorus-preserving gastrectomy: is it meaningful?

Abstract: Preserving CBVN in LPPG for early gastric cancer is a feasible procedure. However, no clinical benefits of the preservation of the CBVN after LPPG are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
(55 reference statements)
1
14
0
Order By: Relevance
“…In gastric cancer surgery, to achieve better lymph node dissection, the liver branch of the vagus nerve is inevitably damaged. Deletion or damage to the vagus nerve branch can result in impaired gallbladder emptying, which in turn may lead to gallstone formation [7, 8]. Also, radical gastrectomy usually involves Billroth II and Roux-en-Y techniques, which eliminate food passing through the duodenum, and may reduce secretion of cholecystokinin and gallbladder activity, promoting cholestasis and gallstone formation [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In gastric cancer surgery, to achieve better lymph node dissection, the liver branch of the vagus nerve is inevitably damaged. Deletion or damage to the vagus nerve branch can result in impaired gallbladder emptying, which in turn may lead to gallstone formation [7, 8]. Also, radical gastrectomy usually involves Billroth II and Roux-en-Y techniques, which eliminate food passing through the duodenum, and may reduce secretion of cholecystokinin and gallbladder activity, promoting cholestasis and gallstone formation [2].…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node dissection during radical gastrectomy is another possible risk factor for gallstone formation and subsequent cholecystectomy. Some studies have shown that the degree of lymph node dissection has an influence on gallstone formation [8]. More involved lymph node dissections are associated with a higher incidence of gallstones and acute cholecystitis following subsequent surgery than with limited or standard lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may represent a putative basis for the benefit of preserving the celiac branch during pylorus-preserving gastrectomy to reduce gastric stasis [2]. However, the benefit was not proven in retrospective analysis, which was likely a manifestation of delayed emptying after pylorus-preserving gastrectomy being primarily associated with a denervated antrum and the function of the pylorus, rather than the emptying function of the duodenum [16].…”
Section: Discussionmentioning
confidence: 99%
“…The celiac branch is also known to be associated with intestinal motility and diarrhea after gastrectomy. However, reports on the ability of celiac preservation to mitigate incidence of diarrhea or weight loss are conflicting [8121314151617]. These discrepancies could be partly explained by possible unnoticed injuries to the vagus nerve during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In gastric operations, reconstruction of the digestive tract may decrease passage of food through the duodenum, which probably decreases cholecystokinin secretion and reduces gallbladder motility, facilitating gallstone formation [ 12 ]. In addition, the hepatic branch of the vagus nerve is unavoidably damaged during surgical operations for gastric cancer because of the need for extended lymphadenectomy; moreover, the absence of or damage to the hepatic branch may cause dysregulation of gallbladder emptying, which may in turn contribute to gallstone formation [ 13 ]. Therefore, individualized and appropriate treatment strategies for CCL in patients with a history of gastrectomy are very valuable because such patients are often encountered in clinical practice.…”
Section: Discussionmentioning
confidence: 99%